Viaporin pommitusta tykkiveneistä Krimin sodassa - A. Park
fyysinen kuvaus: vaaka
Keywords: pommitukset; Krimin sota; laivastot; linnoitukset; purjelaivat; rannikkovedet; sota-alukset; Suomenlinna; tykkiveneet; Suomi, Helsinki, Viapori, Helsinki